Fenomena dan Faktor Perkawinan Semarga - Muslim Pohan (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2021)
Traditionally, there are 3 (three) Batak marriage systems, namely; exogamy, endogamy, and electrograms. Based on these three types, clan marriage is a marriage that is prohibited in Batak customs and culture. Semarga is a condition where one individual and another individual has a blood lineage through the father's line. Family marriages carried out by the Batak Mandailing migrant community in Yogyakarta experienced a shift in meaning from the traditional Batak culture, from an exogamous marriage system to an eleutherogamous marriage system that does not recognize any prohibitions as is the case in the exogamous or endogamous marriage system. The article is field research with a qualitative approach. The method of data collection was carried out by field observations and conducting interviews with informants. The primary sources in this paper are the Mandailing Batak people who marry within the same clan. In addition, interview data were also obtained for traditional leaders, religious leaders, intellectuals, and the surrounding community. The results of the study concluded; Factors that affect clan marriages in the Batak Mandailing migrant community are due to love factors, religious factors, economic factors, educational factors, and cultural factors. Family marriages in the Batak Mandailing migrant community are carried out because the migrant Batak Mandailing community does not believe in taboo things that are local wisdom.